PENGARUH KOMPENSASI DAN PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PALANG MERAH INDONESIA KOTA BANDUNG - Ruhanda Ruhanda (Masoem University, 2018)
This research aims to analyze the performance of employees at the Palang Merah Indonesia in Bandung. This study uses compensation and good corporate governance variables to analyze employee performance using work motivation as an intervening variable. The population in this study were all employees of the Palang Merah Indonesia in Bandung by using a minimum sample of 110 employees after being calculated using the slovin technique with simple random sampling. Data collection methods in the study used primary and secondary data, explanatory surveys, and questionnaires. Data analysis technique in this study uses regression analysis. The purpose of this study was to analyze the direct effect of compensation and good corporate governance on employee performance through motivation as an intervening variable. The results showed that the motivation and compensation variables had a significant positive influence on good corporate governance. Furthermore, the variable good corporate governance shows significant positive results on employee performance.